Crowd Orchestration – An EPS@ISEP 2021 Project - Fohanno, Bleuenn (2021)
The European Project Semester (EPS) is a multicultural and multidisciplinary project-based learning semester offered by a network of providers, including the Instituto Superior de Engenharia do Porto (ISEP). In the spring of 2020/2021, five EPS@ISEP students from different areas of studies and countries — Portugal, Romania, Poland and France — teamed up. Given the disorganization and overcrowding affecting the experience of attendees at large events, the team decided to create a Crowd Orchestration solution for large outdoor festivals. To this end, the team designed “ScanGo” with real time alerts about the number of people in predefined areas, suggestion of alternative activities within the event or indication of the best route to go from one stage to the another. This way, ScanGo also intends to minimize the effects of the undergoing pandemic, allowing people to safely experience open air festivals. This paper reports the different stages of the teamwork, encompassing the preliminary studies and the design of ScanGo, followed by the development and test of a proof-of-concept prototype.